Acupressure and ginger drinks for dysmenorrhea pain among teenage girls - Fajaraina, Adila Awani; Mareta, Reni; Wardani, Septi (Universitas Muhammadiyah Magelang, 2023)
Dysmenorrhea is characterized by abdominal-to-pelvic pain, such as cramps before or at the beginning of menstruation. Overcoming dysmenorrhea can be done with non-pharmacological therapy such as a combination of acupressure and ginger drink. The use of this therapy is limited in the literature. This study aims to apply and determine the effectiveness of acupressure and ginger drink in treating dysmenorrhea. This research uses a case study method using purposive sampling. The samples were two young women aged 14-15 who experienced dysmenorrhea. The intervention was given for several days. The evaluation was conducted after completing the study. The ginger drink contains essential oils, and the content of gingerol in ginger can block prostaglandins so that it can reduce menstrual pain. Community nurses can use this therapy in the course of pain management. Keywords: Acupressure; ginger drink; dysmenorrhea; teenager; pain management